Phytoremediation of perfluorochemicals: A review of its advances, feasibility and limitations - Tang, Kuok Ho Daniel (Universitas Nahdlatul Ulama Surabaya, 2023)
The detection of perfluorochemicals (PFCs) in various environmental compartments has raised attention and driven countermeasures to reduce their prevalence. Phytoremediation provides a feasible option for PFCs removal from the environment. Crops such as maize, carrots, lettuce, tomato and spinach have demonstrated the ability to phytoextract and phytoaccumulate PFCs. The bioconcentration factors (BCFs) of PFCs in plants widely vary with plant types, plant parts, the types of PFCs and the properties of soil. Maize straw for instance was shown to have a high BCF (35.23) for perfluorobutanoic acid in comparison to maize kernel with a BCF of only 0.229 for the same compound. Maize leaves have a BCF of 9.39 for perfluorohexane sulphonic acid and maize roots have a BCF of 8.82 for perfluorooctane sulphonic acid. Carrots were found to degrade fluorotelomers whereas silver birch and long beechfern are good accumulators of numerous PFCs. BCFs of perfluoroalkyl carboxylic acids are usually negatively correlated to the carbon chain lengths due to decreasing aqueous solubilities with increasing carbon chain lengths which impede root uptake of the compounds. PCFs phytoremediation is low cost, less energy intensive, operationally simple and environmentally friendly but has the drawbacks of inconsistent performance, long duration, and lacking evidence on mineralization of perfluoroalkyl substances. The use of non-crop plants for PFCs phytoremediation is promulgated due to concern of food wastage and the biomass generated from phytoremediating plants should ideally be suitable as feedstock for bioenergy production. This review contributes to further advancement of PFCs phytoremediation by addressing its current limitations.